Estimation of physiological parameters on high density plantations and population arrangements of Musa AAA Simmonds - Barrera-Violeth, José Luis; Cartagena-Valenzuela, José Régulo; Nanclares-Gómez, Omar Alonso (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
In Uraba, Antioquia (Colombia), there is a shortage of first-semester fruits and a surplus of second-semester fruits as a result of low or high precipitation, respectively, affecting the value of production. An experiment was established during 2015-2016 in an area representative of the region in order to determine the field distribution and plantation density that maximize the agronomic potential of Musa AAA Simmonds cv. Williams. The population arrangement treatments (rectangle, triangle and double row), planting densities (2,000; 2,500, 3,000 and 3,500 plants/ha) and one control (1,700 plants/ha in a triangle) were evaluated in a complete, random block design with three repetitions. In the phenological phases of floral differentiation, flowering and harvest, the gas exchange was quantified with measurements of the photosynthesis rate, internal CO2 concentration, stomatal conductance, transpiration, vapor pressure deficit, and water use efficiency. The leaf temperature, quantum photosynthesis efficiency and efficient use of radiation were also considered. The yield components and fruit quality were estimated with fruit mass, number of hands, number of fruits, length of the last hand and degree of the second and last hand. The results showed that the density 2,500 plants/ha, distributed in a triangle or double row, promoted the best use of the climate elements associated with photosynthetic activity under the environmental conditions of Uraba, Antioquia.